Spatial analysis of education distribution concerning a watershed money income - Sales, Jomil Costa Abreu [UNESP]; Silva, Camille Vasconcelos [UNESP]; Silva, Darllan Collins da Cunha e [UNESP]; Bitar, Omar Yazbek; Lourenço, Roberto Wagner [UNESP] (Nativa, 2022)
The current study aims to analyze the spatial distribution relationship among schooling indexes, considering the money income of census tracts of the watershed Una river, which is located at Ibiuna, municipality of São Paulo state. The 2010 Population Census and the Ordinary Kriging were used as geostatistical analysis. Kernel test was applied to evaluate schools density. Pearson test demonstrated a correlation between schooling rates and money income on the population older than 20 years, showing that, the smaller the income, the smaller are the schooling levels. Associated with that, the area distribution of the smallest schooling levels are the same with the biggest agricultural vocation. Therefore, in conclusion, understanding the schooling distribution potential in relation to the income is an important management tool for public and social policies.
Análise espacial da distribuição do ensino em função da renda em uma bacia hidrográfica
Keywords: geographic information systems; kriging; schooling; spatial distribution